Thyroid hormones and their placental deiodination in normal and pre-eclamptic pregnancy - Kurlak, L.O.; Mistry, H.D.; Kaptein, E.; Visser, T.J.; Broughton Pipkin, Fiona (Elsevier, 2013)
Pre-eclampsia is associated with lower serum selenium concentrations and glutathione peroxidase expression/activity; total thyroid hormones are also lower. Objectives, study design and main outcome measures: We hypothesised that the placental selenoprotein deiodinase (D3) will be protected in pre-eclampsia due to the hierarchy of selenoprotein biosynthesis in selenium deficiency. Venous blood and tissue from three standardised placental sites were obtained at delivery from 27 normotensive and 23 pre-eclamptic women. mRNA expression and enzyme activity were assessed for both deiodinases (D2 and D3); protein expression/localisation was also measured for D3. FT4, FT3 and TSH concentrations were measured in maternal and umbilical cord blood. Results: No significant differences in D3 mRNA or protein expression between normotensive and pre-eclamptic pregnancies. There was a significant effect of sampling site on placental D3 activity only in pre-eclamptic women (P = 0.034; highest activity nearest the cord). A strong correlation between D3 mRNA expression and enzyme activity existed only in the pre-eclamptic group; further strengthened when controlling for maternal selenium (P < 0.002). No significant differences were observed between groups for any of the maternal thyroid hormones; umbilical TSH concentrations were significantly higher in the pre-eclamptic samples (P < 0.001). Conclusions: D3 mRNA and protein expression appear to be independent of selenium status. Nevertheless, the positive correlation between D3 mRNA expression and activity evident only in pre-eclampsia, suggests that in normotensive controls, where selenium is higher, translation is not affected, but in pre-eclampsia, where selenium is low, enzyme regulation may be altered. The raised umbilical TSH concentrations in pre-eclampsia may be an adaptive fetal response to maximise iodide uptake.